Lactation Management Education For Postpartum Patients At A.M. Parikesit Hospital, Tenggarong - Tri Wahyuni; Mistaratul Wardaniah (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Breast milk is an essential substance that newborns need to fulfill their nutritional needs and develop their body systems. The breastfeeding rate in Indonesia only reaches 80%, which means it is still below the coverage target. Breast milk given exclusively can be a natural contraceptive, reduce the risk of breast cancer, and reduce postpartum bleeding. Therefore, lactation is necessary for smooth and increased breast milk production. Lactation management education for postpartum mothers is needed to provide understanding to mothers so that their motivation to provide exclusive breastfeeding increases, and they can perform lactation correctly. After lactation management education, the mother’s knowledge of lactation management increases, and the attachment between mother and baby also increases.